The study of fruit pulp commercialization: a case study of an association of producers in Paraíba (Research, Society and Development, 2020)
Agribusiness is fundamental for the balance of the Brazilian economy. People look for healthy habits at their table, so the Fruit Pulp Factory located in the rural area of ​​Areia-PB, manufacture pulps for sale in Areia and surrounding regions. To promote this market, innovation and marketing are needed. The use of technologies in the field has become essential to carry out an activity in a planned and effective way. From the planting strategy to the harvest. Thus, the objective of this work was to analyze the commercialization channels used by the fruit pulp factory, maintained by the association - Association for the Development of the Community of Chã de Jardim (ADESCO). For this, research was used on social networks such as Facebook, interviews with those responsible for the factory, visits to YouTube and Instagram channels. After the analysis, it was verified that the factory does not use the potential that social networks have, leaving flaws and opportunities to promote the pulps. The use of strategies such as social networks is a profitable and effective way. The factory should exploit these networks adding more value to its product and obtaining recognition from the company.